The influence of adrenergic stimulation on sex differences in left ventricular twist mechanics - Williams, Alexandra M.; Shave, Rob E.; Cheyne, William S.; Eves, Neil D. (The Journal of physiology, 2017)
Key points Sex differences in left ventricular (LV) mechanics occur during acute physiological challenges; however, it is unknown whether sex differences in LV mechanics are fundamentally regulated by differences in adrenergic control. Using two‐dimensional echocardiography and speckle tracking analysis, this study compared LV mechanics in males and females matched for LV length during post‐exercise ischaemia (PEI) and β1‐adrenergic receptor blockade. Our data demonstrate that while basal rotation was increased in males, LV twist was not significantly different between the sexes during PEI. In contrast, during β1‐adrenergic receptor blockade, LV apical rotation, twist and untwisting velocity were reduced in males compared to females. Significant relationships were observed between LV twist and LV internal diameter and sphericity index in females, but not males. These findings suggest that LV twist mechanics may be more sensitive to alterations in adrenergic stimulation in males, but more highly influenced by ventricular structure and geometry in females. Sex differences in left ventricular (LV) mechanics exist at rest and during acute physiological stress. Differences in cardiac autonomic and adrenergic control may contribute to sex differences in LV mechanics and LV haemodynamics. Accordingly, this study aimed to investigate sex differences in LV mechanics with altered adrenergic stimulation achieved through post‐handgrip‐exercise ischaemia (PEI) and β1‐adrenergic receptor (AR) blockade. Twenty males (23 ± 5 years) and 20 females (22 ± 3 years) were specifically matched for LV length (males: 8.5 ± 0.5 cm, females: 8.2 ± 0.6 cm, P = 0.163), and two‐dimensional speckle‐tracking echocardiography was used to assess LV structure and function at baseline, during PEI and following administration of 5 mg bisoprolol (β1‐AR antagonist). During PEI, LV end‐diastolic volume and stroke volume were increased in both groups (P < 0.001), as was end‐systolic wall stress (P < 0.001). LV twist and apical rotation were not altered from baseline or different between the sexes; however, basal rotation increased in males (P = 0.035). During β1‐AR blockade, LV volumes were unchanged but blood pressure and heart rate were reduced in both groups (P < 0.001). LV apical rotation (P = 0.036) and twist (P = 0.029) were reduced in males with β1‐AR blockade but not females, resulting in lower apical rotation (males: 6.8 ± 2.1 deg, females: 8.8 ± 2.3 deg, P = 0.007) and twist (males: 8.6 ± 1.9 deg, females: 10.7 ± 2.8 deg, P = 0.008), and slower untwisting velocity (males: 68.2 ± 22.1 deg s−1, females: 82.0 ± 18.7 deg s−1, P = 0.046) compared to females. LV twist mechanics are reduced in males compared to females during reductions to adrenergic stimulation, providing preliminary evidence that LV twist mechanics may be more sensitive to adrenergic control in males than in females. Key points Sex differences in left ventricular (LV) mechanics occur during acute physiological challenges; however, it is unknown whether sex differences in LV mechanics are fundamentally regulated by differences in adrenergic control. Using two‐dimensional echocardiography and speckle tracking analysis, this study compared LV mechanics in males and females matched for LV length during post‐exercise ischaemia (PEI) and β1‐adrenergic receptor blockade. Our data demonstrate that while basal rotation was increased in males, LV twist was not significantly different between the sexes during PEI. In contrast, during β1‐adrenergic receptor blockade, LV apical rotation, twist and untwisting velocity were reduced in males compared to females. Significant relationships were observed between LV twist and LV internal diameter and sphericity index in females, but not males. These findings suggest that LV twist mechanics may be more sensitive to alterations in adrenergic stimulation in males, but more highly influenced by ventricular structure and geometry in females.